2019
DOI: 10.1111/jphp.13090
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin attenuates cisplatin-induced renal injury by targeting MAPK and apoptotic pathways

Abstract: These authors contributed equally to the research. AbstractObjective Anti-neoplastic drug cisplatin is prescribed widely for treatment of a variety of malignancies. Its use has been restricted lately due to severe renal toxicity. The purpose of current study was to investigate the effect of pitavastatin (a hypolipidaemic drug) in cisplatin-induced acute kidney injury in rats. Method Male Wistar rats (150-200 g) were treated with different doses of pitavastatin (0.16, 0.32 and 0.64 mg/kg per day p.o.; 10 days).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…One previous study showed that atorvastatin ameliorated contrast-induced nephropathy and reduced the extent of renal tubular cell apoptosis that is associated with the decreased expression of proapoptotic Bax/caspase-3 and increased Bcl-2 [ 17 ]. Another study that demonstrated the renoprotective effects of pitavastatin on cisplatin-induced AKI pointed to suppression of the mitogen-activated protein kinase (MAPK)/NF-kB/inflammation axis and intrinsic apoptotic pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…One previous study showed that atorvastatin ameliorated contrast-induced nephropathy and reduced the extent of renal tubular cell apoptosis that is associated with the decreased expression of proapoptotic Bax/caspase-3 and increased Bcl-2 [ 17 ]. Another study that demonstrated the renoprotective effects of pitavastatin on cisplatin-induced AKI pointed to suppression of the mitogen-activated protein kinase (MAPK)/NF-kB/inflammation axis and intrinsic apoptotic pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have shown the nephroprotective efects of statins, including pitavastatin [45][46][47][48][49][50][51], the specifc involvement of the miR-93/PTEN/Akt/mTOR pathway in mediating these efects has not been elucidated in vivo in the context of xenobiotic-induced kidney injury. Our study is the frst to demonstrate that pitavastatin attenuates TAAinduced kidney damage in rats by regulating this essential signaling cascade.…”
Section: Discussionmentioning
confidence: 98%
“…In these cells, the expression of cleaved caspase‐3 and cleaved PARP increased significantly in a dose‐dependent manner after treatment with fluvastatin at concentrations ranging from 0 to 10 μM at exposure times of 12 hours (Qi et al, 2013). Along with the studies showing that PITA induces apoptosis, there are also researchers stating that its effect on apoptosis is quite indirect (Kaushik et al, 2019; Voss et al, 2021). The requirement of studies to be done in this scope is clear.…”
Section: Discussionmentioning
confidence: 99%